A fas apoptotic inhibitory molecule from Ruditapes philippinarum: Investigation on molecular characterization and functional analysis. Issue 104 (September 2020) - Chen, Lizhu; Li, Bin; Hu, Shunxin; Qiao, Ruiguang; Sun, Chunxiao; Yang, Dinglong
Abstract: In the present study, a fas apoptotic inhibitory molecule (FAIM) was identified from Ruditapes philippinarum (designated as RpFAIM). Multiple alignments and phylogenetic analysis strongly suggested that RpFAIM was a new member of the FAIMs family. The RpFAIM transcripts were constitutively expressed in a wide range of tissues, and dominantly expressed in hemocytes. After V. anguillarum or M. luteus challenge, the expression level of RpFAIM transcripts was significantly induced and reached the maximum level at 6 h and 24 h, respectively. Knockdown of RpFAIM down-regulated the transcript levels of NF-κB signaling genes (e.g. RpIKK, RpIκB, RpNF-κB). The results were roughly similar to those under bacterial stimulation. Moreover, RpFAIM primarily localized in the cell cytoplasm, and its over-expression inhibited the apoptosis of HeLa cells. These results revealed that RpFAIM perhaps regulated the NF-κB signaling pathways positively, which provided a better understanding of RpFAIM in innate immunity. Highlights: A fas apoptotic inhibitory molecule (FAIM) was first identified from the manila clam Ruditapes philippinarum. The expression level of RpFAIM transcripts was significantly induced after challenged with V. anguillarum or M. luteus. RpFAIM had a regulatory effect on NF-κB signaling pathways. RpFAIM primarily localized in the cell cytoplasm and its over-expression inhibited the apoptosis.